A Connected History of Health and Education: Learning Together Toward a Better City. Issue 145 (March 2015) - Howard, Joanne; Howard, Diane; Dotson, Ebbin
Abstract : The infrastructure, financial, and human resource histories of health and education are offered as key components of future strategic planning initiatives in learning cities, and 10 key components of strategic planning initiatives designed to enhance the health and wealth of citizens of learning cities are discussed.